Hysterectomy across Different Occupational Groups of Women in India: A Cross-sectional Study - Gaurav Suresh Gunnal; Sudeshna Roy (Journal of Medical Evidence, 2025)
Aims and Objective: The paper aims to examine the prevalence of hysterectomy amongst 451,853 women aged 25–49 years by different occupation groups in India and seek to identify associated factors. It is a cross-sectional study using bivariate and multivariate analyses. Materials and Methods: Data available in the public domain from the fourth round of the National Family Health Survey, conducted pan-India including both rural and urban areas during 2015–2016 by the Ministry of Health and Family Welfare, Government of India, are used. Descriptive statistical analyses were performed to investigate hysterectomy prevalence across various states and union territories and other independent variables in India. Further, two binary logistic regression models were run to examine the determinants of hysterectomy where the dependent variable had undergone hysterectomy and not undergone hysterectomy. Results: The result revealed that about five in every 100 Indian women had undergone hysterectomy. Excessive menstrual bleeding was the most common underlying condition for undergoing hysterectomy amongst all occupation groups. The prevalence was found to be the highest amongst agricultural women workers who are 32% (odds ratio = 1.320; confidence interval: 1.209–1.440) significantly more likely to undergo hysterectomy compared to other occupation groups. Conclusion: These results raise questions about poor access to quality healthcare services particularly for sexual and reproductive health amongst women working in the agricultural sector.